Beyond 2000: Assessments of the Economy and Policy Recommendations- Social Sector dealing with Technology Policy - Jose A. Magpantay (Philippine Institute for Development Studies (PIDS), 1998)
Departing from the usual indicators of sound economic fundamentals, this paper argues that factors like quality of human resources, competitiveness of the national innovation system, stable political, social and economic institutions, and environmentally-safe and ecologically-sound industrial practices can be alternative conditions for sustainable growth. These are feasible given a sound science and technology framework. This paper focuses on technology policies here and abroad and highlights important lessons from the experience of foreign countries. The paper also discusses specific policy recommendations and specific policy programs necessary in restructuring Philippine industries.
Keywords: 330; science and technology; invention and innovation